EKSISTENSI NURDIN BS DALAM BERKARYA SENI LUKIS - Nessya Fitryona, Erfahmi, Syafwan (Universitas Negeri Padang, 2013)
Among the many leaders of West Sumatra artists who have recorded and on the pillowcase in the creative development of the arts in society today, there are still artists who have recorded figures of its existence. If the research is not done now, the artist traces the West Sumatra would be lost without any data at all. One of them is Nurdin B.S. The purpose of this study was (1) to explain the existence of Nurdin B.S. in art work, (2) to explain the existence of continuity and discontinuity Nurdin B.S. works in painting. Data sources of this study are oral sources as the primary source of direct spoken by informants and written sources as secondary sources. Data were collected using the methods of observation, interviews, documentation and browse the internet. The results showed that Nurdin B.S. has existence in the work of art that is influenced by factors: social institutions; artists factors, and society as a supporting factor. Later it was revealed that Nurdin B.S. experiencing discontinuity and continuity of work due to the condition of the people who do not support and sustain the demands of the economic factor in his artistic life.